Language Play in Postmodern Literature: A Study of Lydia Davis’ Stories - Kemertelidze, Nino; Giorgadze, Meri; Kajaia, Manana (European Scientific Journal, ESJ, 2024)
The paper explores the role of language play in postmodern literature through a close examination of Lydia Davis’ stories. Known for her minimalist style, Davis employs innovative narrative techniques and distinctive word choices to disrupt conventional storytelling and invite readers into a complex interaction with language. The analysis highlights how Davis’ manipulation of narrative structure and stylistic devices – such as fragmentation, repetition, irony, etc. – transforms language from a simple medium of expression into a subject of inquiry. This study examines the function of language play in her stories, emphasizing how Davis’ techniques reflect broader postmodern themes of ambiguity, subjectivity, and the fluid nature of meaning.